2017
DOI: 10.2147/ndt.s150589
|View full text |Cite
|
Sign up to set email alerts
|

The role of new antidepressants in clinical practice in Canada: a brief review of vortioxetine, levomilnacipran ER, and vilazodone

Abstract: Although many branded and generic antidepressants are approved for the treatment of major depressive disorder (MDD) in Canada, efficacy and tolerability differ among patients, and new treatment options are needed. Symptom types (eg, fatigue, energy/motivation, cognition, and functioning), medication type, treatment duration, and the need for maintenance therapy are factors that may influence treatment effectiveness. Three antidepressants, vortioxetine, levomilnacipran extended-release (ER), and vilazodone have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Furthermore, vortioxetine showed a favorable profile in terms of sexual side effects in the studied sample: only one patient (4.5%) reported this specific side effect, and we could not exclude that it was related to other concomitant treatment. In other studies, vortioxetine showed a lower rate of sexual dysfunctions compared to other antidepressants, reported in <2% of vortioxetine‐treated patients (Baldwin et al, 2016; McIntyre, 2017). Although in the present study no significant differences among vortioxetine dosage groups were observed, in other trials, sexual dysfunction was found to be more frequent with higher doses, but always lower than those of selective serotonin reuptake inhibitors (SSRIs) (Jacobsen, Mahableshwarkar, Chen, Chrones, & Clayton, 2015).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, vortioxetine showed a favorable profile in terms of sexual side effects in the studied sample: only one patient (4.5%) reported this specific side effect, and we could not exclude that it was related to other concomitant treatment. In other studies, vortioxetine showed a lower rate of sexual dysfunctions compared to other antidepressants, reported in <2% of vortioxetine‐treated patients (Baldwin et al, 2016; McIntyre, 2017). Although in the present study no significant differences among vortioxetine dosage groups were observed, in other trials, sexual dysfunction was found to be more frequent with higher doses, but always lower than those of selective serotonin reuptake inhibitors (SSRIs) (Jacobsen, Mahableshwarkar, Chen, Chrones, & Clayton, 2015).…”
Section: Discussionmentioning
confidence: 87%
“…Overall, two‐thirds of recruited patients did not report any side effects, while in the other third, the 72.7% experimented gastrointestinal side effects (mainly nausea, vomit, and diarrhea) and the 22.7% gastrointestinal ones associated with other side effects (mainly headache and sweating). Indeed, It is well established that vortioxetine's most common side effect is nausea (affecting more than one in 10 people) (EMA, 2014; McIntyre, 2017), generally with mild or moderate severity related to high dosage and usually decreasing or extinguishing in few weeks (De Bartolomeis, Fagiolini, & Maina, 2016). In the same direction, the duration of side effects, in the present study, slightly exceeded 4 weeks (37.17 ± 33.12 days): conversely, the reported severity of side effects was moderate–severe (36.4% moderate and 36.4% severe), and a worse tolerability was not associated with high doses of vortioxetine.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the reasons for discontinuation are unclear from these data, common problems with SSRIs or SNRIs include sexual dysfunction, weight gain and sleep disturbances [9]. The more recent treatment options for GAD target a reduction of these side effects [12]. These newer compounds include the serotonin modulator and stimulator (SMS) vortioxetine, the melatonergic antidepressant agomelatine, and the serotonergic antidepressant vilazodone.…”
Section: Introductionmentioning
confidence: 99%
“…This study evaluated the antidepressant activity of CTE in CUS rats, and confirmed the efficacy in in vivo models such as FST, SPT, OFT, and NSFT, and confirmed the anti-depressive activity of C. tubulosa in CUS rats which is frequently used for the treatment of kidney deficiency, impotence, and female infertility in TCM. Currently, the most commonly prescribed antidepressants are the serotonin and norepinephrine reuptake inhibitor (SNRI) venlafaxine, followed by the selective serotonin reuptake inhibitor (SSRI) FLX ( Thase et al, 2001 ; Mcintyre, 2017 ). However, these antidepressants have been shown to possess severe side effects including cardiac toxicity, blood pressure, sexual dysfunction, and sleep disorders ( Ferguson, 2001 ; Jin et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%